THE APPLICATION OF SYSTEM THINKING FOR FIRM SUPPLY CHAIN SUSTAINABILITY: THE CONCEPTUAL STUDY OF THE DEVELOPMENT OF THE ICEBERG PROBLEM SOLVING TOOL (IPST) - Al-Homery, Hussein Abdou; Ashari, Hasbullah; Ahmad, Azizah (International Journal of Supply Chain Management, 2019)
Purpose: The purpose of this paper is to provide academics and practitioners theoretical, and conceptual framework of the Iceberg Problem Solving Tool ?IPST? as a generic problem-solving tool for an effective supply chain management process. This leverages Organizational learning, organizational culture and corporate knowledge in implementing changes. The ?IPST? is the moderator between the supply chain business process re-engineering of the process changes and systems thinking approach for improvement.Design/Methodology/approach: A theoretical framework is developed from the systems thinking literature; linking integrated system thinking to firm supply chain sustainability. Theoretical versus practical integrated thinking approaches are applied to contrast the rigid management of sustainability with a model that focuses on relationships and broader indicators of societal supply chain business dynamic issues. Illustrations of the conceptualized framework are presented for discussion and for further empirical research.Findings: The (IPST) the Iceberg Problem Solving Tools is a practical tool for the current repetitive events in complex business environments of the supply chain. The tool helps the business management, in seeing the entire effects of the pining emerging events within the firm's supply chain business process; where small changes in the leverage points of the chain business processes or system process lead to tremendous results in the performance of the firm?s supply chain.Practical implications: Potential firms supply chain crises can arise if the daily business events are not well analyzed this will impact the root causes; by taking the right actions for the right causes of the business events to avoid management quick win failures. The implemented action taken will occur by placing the triggers of the supply chain events in its original form; within the main workflow process; this will have the effect of implementing the best results of the ?IPST? in any supply chain business scenarios. Routines and practices will be based on cross-function process analysis through the whole system flow chart diagram of the supply chain to avoid the pain points of the business events.Originality/value: Within theoretical roots in systems thinking, this paper contributes to the relatively unexplored area of the iceberg model of the system thinking tools as a practical business problem-solving tool; for the complexity of the supply chain business events.Keywords: System thinking, Iceberg model, Flow Chart, Macro Cross functions, Critical Thinking, Supply Chain events, business process reengineering, business problem-solving.